Controversial roles for dexamethasone in glioblastoma – Opportunities for novel vascular targeting therapies. Issue 8 (August 2019) - Dubinski, Daniel; Hattingen, Elke; Senft, Christian; Seifert, Volker; Peters, Kevin G; Reiss, Yvonne; Devraj, Kavi; Plate, Karl H
Glioblastoma is a highly aggressive and treatment resistant primary brain tumor. Features of glioblastoma include peritumoral cerebral edema, the major contributor to neurological impairment. Although the current clinical approach to edema management is administration of the synthetic corticoid dexamethasone, increasing evidence indicates numerous adverse effects of dexamethasone on glioblastoma burden at the molecular, cellular and clinical level. The contradictions of dexamethasone for glioblastoma and brain metastasis therapy are discussed in this article. Finally, alternative strategies for cerebrovascular edema therapy with vascular stabilizing, anti-permeability agents that are either approved or in clinical trials for diabetic retinopathy and macula edema, are addressed.